2020
DOI: 10.1002/ddr.21639
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3‐aryl‐5‐substituted‐coumarin analogues: Synthesis and bioactivity profile

Abstract: Eighteen 3-aryl-5-substituted-coumarins-six 5-acetyloxy-derivatives, six 5-hydroxyderivatives, and six 5-geranyloxy-derivatives-were synthesized, structurally characterized and their antioxidant activity, lipoxygenase inhibitory ability, as well as their cytotoxic activity against human neuroblastoma SK-N-SH and HeLa adenocarcinoma cell lines were evaluated. The 5-acetyloxy-compounds 3a-3f were found to be the best cytotoxic agents among all the compounds studied. The bromo-substituted coumarins 3a and 3b were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…EtOH, using piperidine as base-catalyst, Scheme 44. [71] 7-(2-Chloroquinolin-4-yloxy)-4-methyl-2H-chromen-2-ones, Scheme 45, were synthesized by Balaji et al [72] from substituted 1,3-dichloroquinoline and 7-hydroxy-4-methylcoumarin using conventional or under ultrasonic irradiation conditions. Kavetsou et al [73] described the synthesis of new 3-aryl-5substituted-coumarin derivatives in three steps starting from phenylacetic acid and dihydroxyacetophenone, Scheme 46.…”
Section: Reactivity Of Coumarinmentioning
confidence: 99%
See 1 more Smart Citation
“…EtOH, using piperidine as base-catalyst, Scheme 44. [71] 7-(2-Chloroquinolin-4-yloxy)-4-methyl-2H-chromen-2-ones, Scheme 45, were synthesized by Balaji et al [72] from substituted 1,3-dichloroquinoline and 7-hydroxy-4-methylcoumarin using conventional or under ultrasonic irradiation conditions. Kavetsou et al [73] described the synthesis of new 3-aryl-5substituted-coumarin derivatives in three steps starting from phenylacetic acid and dihydroxyacetophenone, Scheme 46.…”
Section: Reactivity Of Coumarinmentioning
confidence: 99%
“…7‐(2‐Chloroquinolin‐4‐yloxy)‐4‐methyl‐2 H ‐chromen‐2‐ones, Scheme 45, were synthesized by Balaji et al [72] . from substituted 1,3‐dichloroquinoline and 7‐hydroxy‐4‐methylcoumarin using conventional or under ultrasonic irradiation conditions.…”
Section: Coumarin Synthesismentioning
confidence: 99%
“…From a medicinal chemistry point of view, several structural analogues have been extracted from natural sources and/or synthesized. The modifications of the basic skeleton of auraptene to yield similarly biologically active compounds include substitution of the α,β-unsaturated lactone ring with α,β-unsaturated carboxylic acid [ 6 ] and α,β-unsaturated aldehyde moieties [ 7 ], introduction of methoxy groups, halogens, and additional terpenyl chains as substituents of the aromatic ring [ 8 , 9 , 10 ], functionalization of the geranyloxy side chain [ 11 , 12 ], and finally introduction of different substituents in the lactone portion [ 13 , 14 ]. The plethora of literature data related to this suggests that the synthesis and investigation of the pharmacological properties of isosters and structural analogues of auraptene is a field of current and active research with many potential outcomes and practical uses in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 7-geranyloxycoumarin exerted remarkable effects in various inflammatory diseases associated with the activation of the acquired immune system, such as asthma and multiple sclerosis (Askari et al, 2020). Also, recent studies have demonstrated that prenyloxycoumarins are potent inhibitors of different types of LOX isoenzymes (Fiorito et al, 2018;Iranshahi et al, 2012;Jabbari et al, 2017;Kavetsou et al, 2017;Kavetsou et al, 2020).…”
mentioning
confidence: 99%